Penis size: Survey of female perceptions of sexual satisfaction - Eisenman Russell (BMC, 2001)
Abstract Background Does the size of the male penis, in terms of length or width, make a difference in female sexual satisfaction? Method To study the effect of penis width vs. length on female sexual satisfaction, 50 sexually active female undergraduate students were asked which felt better, i. e., was penis width or length more important for their sexual satisfaction. Results None reported they did not know, or that width and length were equally satisfying. A large majority, 45 of 50, reported width was more important (p < .001). Conclusion Implications are discussed, including the fact that the data seem to contradict Masters and Johnson about penis size having no physiological effect on female sexual satisfaction.